Teaching practices of the diploma and baccalaureate: strengthening from the self-evaluation of the Basic General Education Career I and II Cycles of the UNED (Revista Electrónica Calidad en la Educación Superior, 2020)
This essay deepens in changes made in the Teaching Practice of the Diploma and Baccalaureate of the Basic General Education I and II Cycles, of the UNED, Costa Rica, from 2013. It was born as an exercise of self-evaluation of the processes of accreditation to which the Race responds. The changes sought to strengthen the training of skills and abilities in the future professional of primary education, to stimulate a work performance that responds to the demands and changes that today's society requires. The curricular analysis determined that the level of satisfactory achievement was acquired through actions that incorporated in the subjects of the curriculum a greater number of visits to the educational context, application of planning, attention to students and observations of class dynamics.
Keywords: Higher Education; Primary Education; Teaching Practices; Classroom Research; autoevaluation